Estimation of anti-orthopoxvirus immunity in Moscow residents and potential risks of spreading Monkeypox virus - Vladimir A. Gushchin; Vladimir A. Gushchin; Darya A. Ogarkova; Inna V. Dolzhikova; Olga V. Zubkova; Igor V. Grigoriev; Andrei A. Pochtovyi; Andrei A. Pochtovyi; Anna A. Iliukhina; Tatiana A. Ozharovskaia; Nadezhda A. Kuznetsova; Daria D. Kustova; et al. (Frontiers in Immunology, 2022)
WHO has declared the outbreak of monkeypox as a public health emergency of international concern. In less than three months, monkeypox was detected in more than 30 000 people and spread to more than 80 countries around the world. It is believed that the immunity formed to smallpox vaccine can protect from monkeypox infection with high efficiency. The widespread use of Vaccinia virus has not been carried out since the 1980s, which raises the question of the level of residual immunity among the population and the identification of groups requiring priority vaccination. We conducted a cross-sectional serological study of remaining immunity among Moscow residents. To do this, a collection of blood serum samples of age group over 30 years old was formed, an in-house ELISA test system was developed, and a virus neutralization protocol was set up. Serum samples were examined for the presence of IgG antibodies against Vaccinia virus (n=2908), as well as for the ability to neutralize plaque formation with a Vaccinia virus MNIIVP-10 strain (n=299). The results indicate the presence of neutralizing antibody titer of 1/20 or more in 33.3 to 53.2% of people older than 45 years. Among people 30-45 years old who probably have not been vaccinated, the proportion with virus neutralizing antibodies ranged from 3.2 to 6.7%. Despite the higher level of antibodies in age group older than 66 years, the proportion of positive samples in this group was slightly lower than in people aged 46-65 years. The results indicate the priority of vaccination in groups younger than 45, and possibly older than 66 years to ensure the protection of the population in case of spread of monkeypox among Moscow residents. The herd immunity level needed to stop the circulation of the virus should be at least 50.25 – 65.28%.